Eutanasia e donazione di organi. Alcune riflessioni etico-giuridiche su nuove emergenti criticità. (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
This paper presents and critically discusses some profiles that connected the issues of euthanasia and organ donation in recent international debate. The contexts in which new forms of donation, linked to euthanasia, are being discussed, are in particular those in which there is already legislation allowing the practice of euthanasia. However, since these are interesting topics, a critical analysis is proposed, also referring to a possible scenario, which could also concern, in the future, the Italian reality.
Keywords: Euthanasia; organ donation; law; ethics; bioethics